Atorvastatin lipid nanocapsules and gold nanoparticles embedded in injectable thermo‐gelling hydrogel scaffold containing adipose tissue extracellular matrix for myocardial tissue regeneration. Issue 9 (21st October 2019) - Varshosaz, Jaleh; Masoudi, Sepehr; Mehdikhani, Mehdi; Hashemi Beni, Batool; Farsaei, Shadi
Abstract : This study aimed to prepare, optimise, and characterise the novel hybrid hydrogel scaffold containing atorvastatin lipid nanocapsules (LNCs) and gold nanoparticles (NPs) to improve cardiomyoblasts proliferation and regeneration of myocardium. A thermo‐responsive aminated guaran (AGG) hydrogel was prepared to encompass extracellular matrix (ECM) fetched from human adipose tissue. Emulsion phase‐inversion technique was used to obtain LNCs. Biocompatibility, tensile strength, conductivity, and proliferation of human myocardial cells of the optimised formulation were studied. The LNCs have a spherical shape, and the optimised formulation showed a mean particle size of 18.79 nm, the zeta potential of − 11.4 mV, drug loading of 99.99%, and release efficiency percent over 72 h was 18.73%. The injectable thermo‐sensitive hydrogel prepared using 1 w/v% of AGG, 35 w/w% of ECM, ∼0.5 mg/ml of gold NPs and atorvastatin loaded LNCs showed the best physical characteristics. The hybrid scaffold loaded with atorvastatin and gold NPs improved the proliferation of cardiomyoblasts more than sevenfold with enhanced cell attachment to the scaffold. The tensile strength and the conductivity of the scaffold were 300 kPa and 0.14 S/m, respectively. Injectable hybrid adipose tissue prepared by ECM and AGG hydrogel loaded with atorvastatin and gold NPs showed promising physical characteristics for myocardial tissue engineering.